The effect of the cognitive model Daniel in developing thinking and learning the skills of forward and backward rolling in artistic gymnastics for female students of general education. (Journal of the College of Basic Education, 2022)
The effect of Daniel's cognitive model in teaching some basic skills in artistic gymnastics for female students of the Department of Physical Education. The objectives of the research: preparing educational units using Daniel's model in teaching some basic skills in rhythmic gymnastics for female students and identifying the effect of educational units prepared in teaching some basic skills in rhythmic gymnastics for female students in the research sample. The two researchers determined the research community in the intentional way with the students of the first stage, Al-Mustansiriya University, College of Basic Education / Department of Physical Education and Sports Sciences for the academic year 2022.2021, and their number is (140) students divided into four divisions (A, B, C, D) to represent the total community and the research sample was chosen. Randomly and by lottery method from two divisions (D + B), as Division (D) represented the experimental group, with (23) students, and Division (B) represented the control group, with (23) students. The two researchers excluded a number of female students from the research sample. The two researchers conducted the equivalence of the two research groups with the skills under study, then an exploratory experiment was conducted, after which instruction units were designed according to Daniel’s model. The two researchers used the statistical bag to reach the results and in turn to the conclusions, the most important of which is that the Daniel model has a positive effect on the performance of some basic skills in the rhythmic gymnastics for the female students. And Daniel's model helped reveal the students' own abilities, skill level, and learning capabilities. Based on the conclusions reached by the two researchers, they recommend preparing special programs for teachers to train them in preparing the building of educational units using the Daniel model. Directing the teacher and the school to pay attention to the use of educational and teaching methods and to diversify them in a way that suits the needs and content of different sporting events. Emphasis on conducting research and studies of the Daniel model in the sports field for all events, sports and other skills.